Efforts of Establishing Disaster Resilient Villages through Kuliah Kerja Nyata Tematik at Disaster Risk Reduction in Purbalingga District - Sorja Koesuma; Sarjoko Lelono; Chatarina Muryani; Budi Legowo (Institute for Research and Community Services, 2020)
Desa tangguh bencana (Destana) is a program aimed to make a village community prepared for and resilient to disasters. The Destana program was initiated by the National Disaster Management Agency (BNPB) decreed by the Regulation of the head of BNPB No. 1/2012. A village represents the bottom line in the government system and therefore the capacity building for disaster resilience starts from the villages. The number of villages in Central Java reaches 8559 villages, while BNPB, BPBD Province, BPBD Regency/City can only launch Destana on average 30 villages each year from 2013 - 2018. As a result, it takes quite a long time to forming Destana in all villages in Central Java. Therefore, the role of universities, in particular the state universities in forming Destana, is really needed. One of the activities in the formation of Destana was in the kuliah kerja nyata tematik program (KKN PRB) conducted in Purbalingga Regency in 2 villages that were prone to landslides. Provisioning for students refers to Perka BNPB Number 1/2012 by implementing 20 Destana indicators. Gunungwuled village and Panusupan village were the two villages where the KKN PRB done by 10 students each. For 45 days students could build several indicators, i.e. making disaster risk maps calculated based on hazard maps, vulnerability maps, and capacity maps. Next, they made a Landslide Contingency Planning Document with residents and relevant stakeholders. The Village Disaster Risk Reduction Forum consisting of various community components and the BPBD of Purbalingga Regency was also formed. Afterwards, the capacity building activities to the community against disasters were conducted. Finally, an early warning system for landslides in areas with potential landslides was created and warning signs for landslide-prone areas and evacuation route signs were installed. With the help of KKN PRB, the Panusupan village and Gunungwuled village have now become disaster resilient villages.